Cholera in Papua New Guinea and the importance of safe water sources and sanitation - Andrew Greenhill; Paul Horwood (World Health Organization Regional Office for the Western Pacific, 2012)
The recent outbreak of cholera in Papua New Guinea (PNG) has resulted in a large number of illnesses with a relatively high case fatality ratio (3.2%). Access to adequate sanitation and safe water is very low in PNG and has undoubtedly contributed to the spread of cholera within the country.